The Upper Stratospheric Solar Cycle Ozone Response - W. T. Ball; E. V. Rozanov; J. Alsing; D. R. Marsh; F. Tummon; D. J. Mortlock; D. Kinnison; J. D. Haigh (Geophysical Research Letters)
Abstract The solar cycle (SC) stratospheric ozone response is thought to influence surface weather and climate. To understand the chain of processes and ensure climate models adequately represent them, it is important to detect and quantify an accurate SC ozone response from observations. Chemistry climate models (CCMs) and observations display a range of upper stratosphere (1–10 hPa) zonally averaged spatial responses; this and the recommended data set for comparison remains disputed. Recent data‐merging advancements have led to more robust observational data. Using these data, we show that the observed SC signal exhibits an upper stratosphere U‐shaped spatial structure with lobes emanating from the tropics (5–10 hPa) to high altitudes at midlatitudes (1–3 hPa). We confirm this using two independent chemistry climate models in specified dynamics mode and an idealized timeslice experiment. We recommend the BASICv2 ozone composite to best represent historical upper stratospheric solar variability, and that those based on SBUV alone should not be used.